Frequency and impact on renal transplant outcomes of urinary tract infections due to extended-spectrum beta-lactamase-producing Escherichia coli and Klebsiella species - Brune, Jakob E.; Dickenmann, Michael; Sidler, Daniel; Walti, Laura N.; Golshayan, Déla; Manuel, Oriol; Haidar, Fadi; Neofytos, Dionysios; Schnyder, Aurelia; Boggian, Katia; Mueller, Thomas F.; Schachtner, Thomas; et al. (Frontiers in Medicine, 2024)
Background: Enterobacterales are often responsible for urinary tract infection (UTI) in kidney transplant recipients. Among these, Escherichia coli or Klebsiella species producing extendedspectrum beta lactamase (ESBL) are emerging. However, there are only scarce data on frequency and impact of ESBL-UTI on transplant outcomes. Methods: We investigated frequency and impact of first-year UTI events with ESBL Escherichia coli and/or Klebsiella species in a prospective multicenter cohort consisting of 1482 kidney transplants performed between 2012 and 2017, focusing only on 389 kidney transplants having at least one UTI with Escherichia coli and/or Klebsiella species. The cohort had a median follow-up of four years. Results: In total, 139/825 (17%) first-year UTI events in 69/389 (18%) transplant recipients were caused by ESBL-producing strains. Both UTI phenotypes and proportion among all UTI events over time were not different compared with UTI caused by non-ESBL-producing strains. However, hospitalizations in UTI with ESBL-producing strains were more often observed (39% versus 26%, p=0.04). Transplant recipients with first-year UTI events with an ESBL-producing strain had more frequently recurrent UTI (33% versus 18%, p=0.02) but there was no significant difference in one-year kidney function as well as longer-term graft and patient survival between patients with and without ESBL-UTI. Conclusions: First-year UTI events with ESBL-producing Escherichia coli and/or Klebsiella species are associated with a higher need for hospitalization but do neither impact allograft function nor allograft and patient survival.